Slab Quality and Environmental Degradation with The Addition of Additives and Coagulant - Afriyani Zulyanti; Amin Rejo; Farry Apriliano Haskari; Afrizal Vachlepi (Sriwijaya Journal of Environment, 2017)
Abstract : This research used ammonium chloride at doses of 0%, 0.15%, 0.30% and 0.45% with 0% dose, 0.15%, 0.30% and 0.45% while formic acid and liquid smoke coagulants.  The objective of this research is to determine the effects of the addition of additives (NH4Cl) and the type of coagulants on the quality slab degradation. The observed parameters were the value of dry rubber content (%), initial plasticity (Po), plasticity retention index (PRI), ash content (%), volatile matter (%) and Mooney viscosity. The results showed that doses ammonium chloride and coagulants affected to the value of dry rubber content (%), initial plasticity (Po), plasticity retention index (PRI), ash content (%), volatile matter (%) and Mooney viscosity. The treatment dose 0.45% ammonium chloride with coagulant has the best combination treatment reason it produced slab with dry rubber content 46.517%, initial plasticity 45, plasticity retention index 94, ash content 0.278%, volatile matter 0.604% and Mooney viscosity 72.Keywords: Ammonium chloride, coagulants and slab. Abstrak (Indonesian) : Penelitian ini menggunakan amonium klorida dengan dosis 0%, 0,15%, 0,30% dan 0,45% sedangkan jenis koagulan asam format dan asap cair.  Penelitian ini dilakukan untuk mengetahui pengaruh penambahan zat aditif (NH4Cl) dan jenis koagulan terhadap degradasi mutu sleb.  Parameter yang diamati adalah kadar karet kering (%), plastisitas awal (Po), indeks retensi plastisitas (PRI), kadar abu (%), kadar zat menguap (%), viskositas Mooney. Hasil penelitian menunjukkan bahwa penambahan dosis amonium klorida dan jenis koagulan berpengaruh nyata terhadap kadar karet kering (%), plastisitas awal (Po), indeks retensi plastisitas (PRI), kadar abu (%), kadar zat menguap (%), viskositas Mooney. Perlakuan dosis amonium klorida 0,45% dengan koagulan asam format merupakan perlakuan terbaik menghasilkan kadar karet kering 46,517%, plastisitas awal 45, indeks retensi plastisitas 94, kadar abu 0,278% , kadar zat menguap 0,604% dan viskositas Mooney 72.Kata Kunci: Amonium klorida, koagulan dan sleb.